(untitled) (PerCursos, 2023)
Introduction: The increase in mobile device users aged > 60 years reflects a transformation in the information and communication technology (ICT) area. Supporting older adults in their digital literacy is a complex task. New skills for the digital age should be developed. Objective: To describe the sociodemographic characteristics of older adults on a digital literacy program, including patterns of use, reasons for learning, in addition to the difficulties and benefits reported regarding the use of technology. Methodology: A quantitative and qualitative study based on a digital literacy program within a U3A context involving professionals in the fields of gerontology and computing was conducted. Result: The program involved 317 older adults, most of whom were women (64.5%). Mean age of participants was 60-74 years (82%). Regarding characteristics, 44.2% were married, 40.7% had finished high school, 77.3% were retired, 65.1% earned ≤ 4 minimum wages, and 74.1% were not engaged in paid employment. Prior to participation, despite the high frequency of smartphone use (87.6%), 77.9% reported having a poor user experience. The most prevalent purposes for using smartphones were “Communication” (93.3%), “Strengthening affectional bonds with family and friends” (66.2%) and “Search for general information” (48.7%). The assessment of self-efficacy revealed that participants lacked competence for complex activities. Conclusion: The interest of older Brazilians in using smartphones is clear. Therefore, understanding previous competencies, as well as the obstacles faced by this group, is pivotal in aiding the process of digital inclusion.